Gender differences in financial well-being among college students - Falahati, Leila; Paim, Laily (American-Eurasian Network for Scientific Information, 2011)
Financial satisfaction and its impact on the quality of life have received considerable attention in recent decades. A large number of studies have attempted to identify the dimensions of financial well-being and financial behavior among various groups in relation to the development of personal financial well-being. The majority of studies on personal financial satisfaction and financial behavior among adolescents reveal notable sex differences. There is evidence that men and women's perceptions differ and that they are not necessarily only influenced by economic factors, but also by social and psychological issues. To identify gender differences in financial well-being, this study focuses on the perceived financial well-being of Malaysian college students. This study was carried out under (IRPA) funding. Data were collected from students in public and private Malaysian universities. The multi stage stratified random sampling technique was used. A total of 11 universities were randomly selected for the study and 350 questionnaires were distributed to students through the student affairs section of the respective university. Data were collected using self-administered questionnaires. Financial well-being was measured by a six-item scale. The students were asked to rate those six items on a scale of one (not satisfied at all) to nine (very satisfied). The items statements include the amount of saving, financial situation, ability to purchase, saving for emergency expenses, skill to manage money, and ability to spend. The results revealed that there were significant gender differences among Malaysian college students concerning financial matters. The results indicate that Malaysian female students have a significantly higher level of financial satisfaction compared to male students. Female students have a lower level of financial knowledge and late age financial socialization compared to male students. The results showed that primary socialization agents were the strongest predictor of financial well-being among male students while financial problems were the strongest predictor among female students. Mediation analysis confirmed the mediation effect of financial problems in the association between predictors and financial well-being.